Influence of inter-cropping systems and nitrogen levels on the growth and yield of maize - Thenua, O.V.S.; Singh, Jasbir (Annals of Agricultural Research, 2016)
A field investigation was conducted at Agronomy Research Farm, A. S. College, Lakhaoti, Bulandshahr (UP) during kharif season of 2009 and 2010 to study the performance of maize as influenced by maize + soybean intercropping and nitrogen levels. The treatments consisted of combination of five cropping systems (C1) maize (sole crop), (C2) soybean (sole crop), (C3) maize + soybean ( 1: 1 replacement series), (C4) maize + soybean (1: 1 additive series.), (C5) maize + soybean (1 : 1 mixed seed) in main-plots; four Nitrogen Levels (N0) Control, (N1) 40 kg N/ha, (N2) 80 kg N /ha, (N3) 120 kg N /ha in sub-plots in factorial randomized block design and replicated thrice during the kharif season. The maize variety Uttam Azad and soybean variety Alankar were used. The soil of the experimental site was sandy loam in texture with adequate internal drainage. Growth parameters of maize, viz. plant stand, plant height and dry matter production recorded higher in intercropped maize as compared to sole crop of maize. The yield attributes of maize including cob, number of grains per cob, shelling per cent and test weight were significantly improved under soybean intercropped maize over sole maize. The yield was noticed higher (37.2 & 37.8 q/ha) with soybean (additive series,1:1 ratio) as compared to sole crop (32.9 and 33.5 q/ha). Almost all the yield attributes of maize were significantly increased by nitrogen application as compared to control.